Effects of exposure to elevated temperature and different food levels on escape response and metabolism of early stages of white seabream, Diplodus sargus - Almeida, João Carlos Gil (2021)
Dissertação de Mestrado apresentada no ISPA – Instituto Universitário para obtenção de grau de Mestre na especialidade de Biologia Marinha e Conservação